Effects of preconditioning with TNFα and IFNγ in angiogenic potential of mesenchymal stromal cell-derived extracellular vesicles - Cavallero, Sophie; Dekali, Samir; Guitard, Nathalie; Théry, Héléne; Hélissey, Carole; François, Sabine (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stromal cells (MSCs) have demonstrated therapeutic properties both in vitro and in vivo to treat various diseases, including anti-inflammatory, immunomodulatory and pro-angiogenic effects. These therapeutic effects are mediated by their secretome composed of soluble factors and extracellular vesicles (EVs). The composition of EVs reflects the molecular and functional characteristics of parental cells. MSC preconditioning can alter the composition of EVs, thereby influencing their therapeutic potential. MSCs were subjected to preconditioning with two cytokines, TNFα and INFγ. Following 24 hours of preconditioning, MSC-EVs secreted into the culture supernatant were isolated through tangential filtration. Particle concentration and size distribution were measured by nanoparticle tracking analysis, and the surface antigen expression of the EV-specific CD63 was quantified via Enzyme Linked ImmunoSorbent Assay. The angiogenic potential of MSC-EVs obtained after preconditioning MSCs was assessed by the analysis of their protein composition and their influence on human umbilical vein endothelial cell (HUVECs) proliferation, migration, and tube-forming ability. Preconditioning with TNFα and INFγ did not influence the MSC-EV profile but did induce changes in their protein content. Indeed, the expression of pro-angiogenic proteins increased in EVs from preconditioned MSCs compared to EVs from no-preconditioned MSCs. EVs from preconditioned MSCs tend to stimulate HUVEC migration, proliferation and tube-forming ability. These observations imply the presence of a pro-angiogenic potential in EVs obtained after preconditioning of MSCs with TNFα and IFNγ. In conclusion, it appears that the pro-angiogenic potential of EVs is enhanced through preconditioning of MSCs with TNFα and IFNγ. The use of these MSCs-EVs in therapy would circumvent the limitations of current cell-based therapies. Indeed, the therapeutic potential of MSC-EVs presents an attractive strategy for exploiting the clinical benefits of MSC therapy. For example, in the field of regenerative medicine, the exploitation of cell-free therapy using highly pro-angiogenic MSC-EVs is of great interest.